Protein‐losing enteropathy and erythema caused by egg allergy in a breast‐fed infant. Issue 5 (28th January 2016) - Higuchi, Ryuzo; Booka, Mina; Suzuki, Hiroyuki; Tsuno, Hiroshi
Abstract: A 4‐month‐old breast‐fed girl presented with poor weight gain, and had edema and repeated erythema from 5 months of age. The diagnosis of protein‐losing enteropathy (PLE) was confirmed on 99m Tc‐labeled human serum albumin scintigraphy. Specific IgE radioallergosorbent test was class 3 for egg white, class 2 for egg yolk, and negative for other foods. Elimination of egg from the mother's diet and oral epinastine hydrochloride treatment and sodium cromolyn improved hypoalbuminemia, hypogammaglobulinemia, and erythema. PLE and erythema coincident in a breast‐fed infant suggests that IgE‐mediated allergy may play a leading role in some cases of PLE due to food allergy in infants.